2022
DOI: 10.1136/jitc-2021-003082
|View full text |Cite
|
Sign up to set email alerts
|

Combined IL-2, agonistic CD3 and 4-1BB stimulation preserve clonotype hierarchy in propagated non-small cell lung cancer tumor-infiltrating lymphocytes

Abstract: BackgroundAdoptive cell transfer (ACT) of tumor-infiltrating lymphocytes (TIL) yielded clinical benefit in patients with checkpoint blockade immunotherapy-refractory non-small cell lung cancer (NSCLC) prompting a renewed interest in TIL-ACT. This preclinical study explores the feasibility of producing a NSCLC TIL product with sufficient numbers and enhanced attributes using an improved culture method.MethodsTIL from resected NSCLC tumors were initially cultured using (1) the traditional method using interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 55 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…IL-2 is a cytokine responsible for the growth, proliferation, and survival of T-cells. IL-2 has been shown to play a vital role in the regulation of CD8+ T-cells to maintain their reactivity against tumor cells [ 35 , 36 ]. Our data suggests that IL-1B may play a more dominant role in regulating T-cell recruitment into the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…IL-2 is a cytokine responsible for the growth, proliferation, and survival of T-cells. IL-2 has been shown to play a vital role in the regulation of CD8+ T-cells to maintain their reactivity against tumor cells [ 35 , 36 ]. Our data suggests that IL-1B may play a more dominant role in regulating T-cell recruitment into the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…The immune escape of tumor cells is closely related to T cells, which regulate the body's immune response [ 29 ]. IFN-γ, IL-2 and TNF-α are important cytokines that regulate immune response and play an important role in the body's immune response, which secreted by T cells activation [ [30] , [31] , [32] ]. It was found that the levels of IFN-γ, IL-2 and TNF-α increased significantly after transfection of si-circTLK1 in co-cultured cells.…”
Section: Discussionmentioning
confidence: 99%
“…Innovative TIL cultivation methods have emerged to precisely and rapidly obtain tumor-reactive TILs in the laboratory. In the pre-Rapid Expansion Protocol (pre-REP) phase, block-processed tumors are co-cultured with IL-2, CD3 antibodies, and 4-1BB antibodies to activate T cells, enhancing the success rate of TIL cultivation ( 121 , 123 , 124 ). This approach shortens the cultivation time and increases the number of expanded CD8 + TILs ( 123 ).…”
Section: Tils Preparationmentioning
confidence: 99%
“…In the pre-Rapid Expansion Protocol (pre-REP) phase, block-processed tumors are co-cultured with IL-2, CD3 antibodies, and 4-1BB antibodies to activate T cells, enhancing the success rate of TIL cultivation ( 121 , 123 , 124 ). This approach shortens the cultivation time and increases the number of expanded CD8 + TILs ( 123 ). Generally, TILs producing IFN-γ in co-culture with autologous tumor cells are considered tumor-reactive and are then expanded further, although this requires a longer cultivation time ( 125 , 126 ).…”
Section: Tils Preparationmentioning
confidence: 99%